The Effects of Marble Dust on the Rheological and Mechanical Properties of Shotcrete - Shaaban, M. (Engineering, Technology & Applied Science Research, 2020)
Recycling industrial waste materials has become an environmental and economic necessity. The utilization of these materials to develop concrete contributes not only to their disposal, but also to the preservation of the environment. This study attempted to evaluate the properties of sprayed concrete with Marble Dust (MD) as partial replacement of concrete components. For this purpose two series of concrete mixtures were prepared: the first series included six mixtures containing MD as cement replacement with percentages of 5%, 10%, 15%, 20%, 25%, and 30% by weight, the second series included six mixtures containing 5%, 10%, 15%, 20%, 25%, and 30% of MD as replacement for sand. Also, conventional concrete mixture with 100% cement and 100% sand was produced as control mixture. Rheological and mechanical properties as pumpability, build-up thickness, rebound percentage, adhesion strength, and compressive and tensile strength were studied. In general, the results indicate that use of MD improves shotcreting as an application and shotcrete’s performance.